2013
DOI: 10.1074/jbc.m113.493957
|View full text |Cite
|
Sign up to set email alerts
|

Transient Exposure of Pulmonary Surfactant to Hyaluronan Promotes Structural and Compositional Transformations into a Highly Active State

Abstract: Background: Pulmonary surfactant is inactivated under pathological conditions, making clinical surfactants fail in respiratory therapies. Results: Exposure to a hyaluronan meshwork modifies the structure and composition of surfactant. Conclusion: Transient exposure of surfactant to hyaluronan leads to a higher resistance to inactivation. Significance: Understanding the effects of polymers as additives in surfactant will allow the development of new therapeutic options.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 52 publications
(78 reference statements)
1
21
0
1
Order By: Relevance
“…It was therefore concluded that the reversion mechanism is somehow general for surfactants and not specific for the inhibitory agents tested. Further studies concluded that exposure to polymers above concentration thresholds at which polymer chains entangle causes substantial changes in surfactant membrane structure [ 38 ]. These changes include extensive packing, dehydration and structural depuration ending in a highly active structure able to overpass inhibition by serum or meconium.…”
Section: Discussionmentioning
confidence: 99%
“…It was therefore concluded that the reversion mechanism is somehow general for surfactants and not specific for the inhibitory agents tested. Further studies concluded that exposure to polymers above concentration thresholds at which polymer chains entangle causes substantial changes in surfactant membrane structure [ 38 ]. These changes include extensive packing, dehydration and structural depuration ending in a highly active structure able to overpass inhibition by serum or meconium.…”
Section: Discussionmentioning
confidence: 99%
“…The biological plausibility and empirical evidence of the inhibition of lung surfactant function by inhaled substances or by blood components reaching the alveolar airspaces, are high. Studies have been conducted for a number of substances including airborne nanoparticles ( Chen et al, 2017 , Yang et al, 2018 , Larsen et al, 2020 ), airborne chemicals ( Da Silva et al, 2021 ), and biological components such as albumin, cholesterol meconium, and serum ( Zuo et al, 2006 , Lopez-Rodriguez et al, 2011 , Lopez-Rodriguez et al, 2012 , Lopez-Rodriguez et al, 2013 , Zhang et al, 2012 , Autilio et al, 2021 , Gómez-Gil et al, 2009 , Lugones et al, 2018 , Gunasekara et al, 2005 ). For impregnation spray products, the inhibition of lung surfactant function has been reported across multiple methods in vitro , such as the lung surfactant bioassay ( Sørli et al, 2018 ), the capillary surfactometer ( Sørli et al, 2016 ), the pulsating bubble surfactometer ( Tashiro et al, 1998 ), and the Langmuir trough ( Duch et al, 2014 , Larsen, et al, 2014 ).…”
Section: Biological Applicability Domain Of Aop 302mentioning
confidence: 99%
“…However, these interactions are so far basically unexplored although a direct topographical relationship is obvious (Figure 1). One main component of the glycocalyx, hyaluronan, known to be secreted by AEII cells in vitro [27,28], has been shown to improve the biophysical (surface tension reducing) activity of surfactant in vitro and in vivo [29][30][31][32]. Thus, hyaluronan may have therapeutic potential in lung diseases where surfactant inactivation is a major pathophysiological event.…”
Section: Interactions Between Surfactant and The Glycocalyxmentioning
confidence: 99%